Labour markets in transition : the case of Eastern Europe - Fleisher, Belton M. (International journal of manpower, 2002)
Labour markets in transition: the case of Eastern Europe. In 1989 a political revolution in the Soviet Union and its Eastern Europeansatellites led to the dismantling of Communist controls and transition toward freemarkets in goods and services and factors of production.